Selection of 12‐Hour Sustained‐Release Acetaminophen (Paracetamol) Formulation Through Comparison of Pharmacokinetic Profiles of 4 Sustained‐Release Prototype Formulations and Standard Acetaminophen Formulation: An Open‐Label, Randomized, Proof‐of‐Principle Pharmacokinetic Study - Yue, Yong (Clin Pharmacol Drug Dev, 2017)
Acetaminophen (APAP; paracetamol), a widely used analgesic and antipyretic, is available in modified‐release and immediate‐release (IR) formulations requiring 3‐ or 4‐times‐daily dosing. This phase 1 open‐label crossover study compared pharmacokinetic profiles of single 2000‐mg doses of 4 different sustained‐release (SR) formulations of APAP (designed to allow twice‐daily dosing) against two 1000‐mg doses (taken 6 hours apart) of standard IR APAP in 14 healthy volunteers. The primary end point was duration of time that plasma APAP concentration exceeded a plasma concentration (T(C)) of 4 μg/mL. Of the 4 SR APAP formulations studied, a single 2000‐mg dose of a bilayer SR formulation had the longest mean T(C>4μg/mL) (8.1 hours), similar to that of 2 doses of IR APAP (8.3 hours). Mean T(C>4μg/mL) was 7.3 hours with a single‐layer SR APAP, 7.5 hours with another single‐layer SR APAP formulation using a different excipient, and 7.1 hours with an enteric‐coated SR APAP coupled with a fast‐dissolving IR APAP. Secondary pharmacokinetic analyses showed a similar extent of absorption and lower peak concentration for the bilayer SR formulation compared with IR APAP. Adverse events were all mild. Based on these results, the bilayer SR APAP formulation was selected for further development.